ANALISIS ROA DAN ROE TERHADAP PROFITABILITAS BANK DI BURSA EFEK INDONESIA - NUZUL IKHWAL (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2016)
The research theme is the financial and banking institutions. The purpose of this study was to examine the influence of return on assets and return on equity on profitability in banking companies listed in Indonesia Stock Exchange. The data used in this research is secondary data from the financial statements on ten banking company in the Indonesia Stock Exchange. A method of data analysis used in this research is the multiple regression models. The study found that simultaneous return on assets and return on equity effect on the profitability of the banking companies listed in Indonesia Stock Exchange. Similar findings were also found partial test results. This indicates that the return on assets and return on equity are variables to consider for investors before making an investment decision. Partial variable ROA significant effect on profitability because the value t-count > t-table that is equal to 3.254 > 1.667 with a significance value of 0.02 < 0.05, ROE variables have a significant negative effect on profitability due to the value table-t > t-count amounting to -2.250 > 1.667 with significant value 0.015 < 0.05, and variable ROA and ROE jointly affect the profitability indicated by the value of the larger F-count 5.548 > 3.191 with significance value of 0.007.